Sacral Neuromodulation for Fecal Incontinence - Matzel, Klaus; Bittorf, Birgit Renate (Springer Science+Business Media, 2020)
Sacral neuromodulation/neurostimulation (SNM/SNS) has evolved to be central to the armamentarium for the treatment of fecal incontinence. Minimally invasive, it involves electrical stimulation of the sacral nerves by implanted pulse generator. Despite the fact that the exact mechanisms of action and the involved neural pathways are not yet fully understood, SNM has gained wide acceptance among colorectal surgeons. Reasons for this are manifold: its potential to influence several factors contributing to the maintenance of continence, the availability of a reliable pre-implant test, very low surgical risk and comorbidity, a sustained clinical benefit, and a wide range of indications for conditions leading to fecal incontinence. In fact, fecal incontinence of any etiology (except complete spinal cord injury) and any severity has been treated successfully. A quarter century after its introduction in coloproctology, studies on the long-term outcome confirm SNM’s reliability and effectiveness, resulting not only in an improvement in clinical symptoms but also in quality of life.
CRIS-Team Scopus Importer:2025-10-16
Keywords: Fecal incontinence; Neuromodulation; Sacral nerve stimulation; Sacral neuromodulation